Strengthening the competitiveness of MSMEs through creative industries and digital transformation from a sustainable economic perspective - Abdul Fikri; Rindi Antika; Moh. Arif Hidayat; Kamal Ludin (Privietlab, 2026)
creative industry and Micro, Small, and Medium Enterprises (MSMEs) are strategic sectors that contribute significantly to national economic development. The development of the creative industry, supported by innovation, creativity, and the use of digital technology, has opened up opportunities for MSMEs to increase their competitiveness and expand their market reach. This study aims to analyze the role of the creative industry in enhancing the competitiveness of local MSMEs, identify supporting and inhibiting factors for their development, and formulate strategies that can encourage sustainable economic growth. The research used a qualitative approach using case studies and literature review. Data were obtained through observation, documentation, and review of various relevant scientific sources. Data were then analyzed using an interactive analysis model that includes data reduction, data presentation, and conclusion drawing. The results indicate that creativity, product innovation, human resource quality, and the use of digital technology are the main factors determining the success of creative industry-based MSMEs. Digitalization through social media and marketplaces has been proven to increase marketing effectiveness, expand market access, and strengthen relationships with consumers. However, MSME development still faces various challenges, such as limited capital, low digital literacy, lack of managerial skills, and high levels of business competition. Therefore, synergy between the government, academia, the business world, and the community is needed to create an ecosystem that supports the development of the creative industry and MSMEs. By strengthening human resource capacity, increasing access to financing, accelerating digital transformation, and fostering sustainable innovation, the creative industry and local MSMEs have the potential to become key pillars in realizing inclusive, competitive, and sustainable economic growth in Indonesia.